PREVALENCE OF NEUROLOGICAL MANIFESTATION LUMBAR OSTEOCHONDROSIS IN PRIMARY POPULATION OF KEMEROVO REGION - TELEUTS - A. V. Osipov; A. G. Chechenin; A. V. Kolbasko; A. L. Onishchenko (Acta Biomedica Scientifica, 2013)
In population based study were determine the prevalence of lumbar osteochondrose in teleuts population which are the aboriginal in Kemerovo region. It is shown, that the frequency of lumbar osteochondrose are different, depended from male, age, social status, profession and residence. The frequency of vertebral and extravertebral implications of lumbar osteochondrose is defined.